New psychoactive substances in Nigeria: A call for more research in Africa - Emeka W. Dumbili; Ikenna D. Ebuenyi; Kenneth C. Ugoeze (Elsevier, 2021)
Media reports indicate that New Psychoactive Substances (NPS) is widespread in Nigeria and Africa, but little empirical research has been conducted on this. Also, contemporary studies on NPS have focused on Global North, precluding Africa. This may not be unrelated to the 'non-classical packaging' of NPS in homemade herbal mixtures and drug cocktails in the continent. This mini-review highlights the types of non-classical NPS available in Nigeria and calls for comprehensive and coordinated research that will map onto the availability, types, patterns, and motives for taking NPS among Nigerians to be conducted. This will facilitate the design of evidence-based harm reduction strategies to mitigate the challenges posed by NPS. Various substances that are packaged in non-classical forms and used 'to get high' are readily available. Some users take Gutter-Water (a cocktail of tramadol, cannabis, codeine, and vodka) and Monkey-Tail (a cocktail of homemade gin, cannabis seeds, leaves, stems, and roots) while others use 'La Casera Apple Drink' (carbonated soft drink) mixed with 'Tom-Tom' (menthol-flavoured candy). Other available non-conventional substances include smoking the whitish part of lizard dung or dry human faeces, dry cassava and pawpaw leaf/seeds, Zakami (Datura metel) seeds, Moringa (Zogale) leaf and inhaling/sniffing burnt tyres, hydrogen sulphide gas (sewer gas) and nail polish. Furthermore, we found that some people drink a mixture of bleach (sodium hypochlorite solution) and carbonated soft drinks and 10-day old urine as psychoactive substances. The motivations for the use of these substances include pleasure and prolonged intoxication. Studies should be conducted in all the regions of Nigeria and Africa to determine the availability, types, and extent to which NPS and other non-classical substances are available and used. This will facilitate the inclusion of these NPS to the World Drug Report and help in designing public health interventions in these settings.